2008
DOI: 10.1002/ange.200802466
|View full text |Cite
|
Sign up to set email alerts
|

Zum Mechanismus der enzymatischen Chlorierung von Tryptophan

Abstract: [8] und für die Tryptophan-7-Halogenase RebH aus der Rebeccamycinbiosynthese gezeigt werden konnte.[9] Allerdings müssen noch weitere Faktoren eine Rolle spielen, da die Chlorierung von Tryptophan durch Chloramin (oder HOCl) in Lösung nicht gelingt. [10,11] Chloramin ist ein schwächeres Halogenierungsreagens als HOCl [12] und laut quantenchemischen Rechnungen verringert die Bildung von N-Chloramin die Elektrophilie der Chlorspezies, d. h., die Ladung Q(Cl) wird auf À0.07 im Vergleich zu Q(Cl) = + 0.017 in frei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 16 publications
(32 reference statements)
0
6
0
1
Order By: Relevance
“…A lysine (K79) and a glutamate residue (E346) are located close to the substrate, and both are absolutely required for enzyme activity ( Figure 2). [10,11] The lysine residue is suggested to react with the hypochlorous acid to form a chloramine as the halogenating intermediate. [9] Flecks et al [11] suggested that a concerted interaction of hypochlorous acid with the lysine and the glutamate residue should increase the electrophilicity of the chlorine species and in addition ensure the correct positioning of the chlorine species for the regioselective incorporation of chlorine into the indole ring of tryptophan.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A lysine (K79) and a glutamate residue (E346) are located close to the substrate, and both are absolutely required for enzyme activity ( Figure 2). [10,11] The lysine residue is suggested to react with the hypochlorous acid to form a chloramine as the halogenating intermediate. [9] Flecks et al [11] suggested that a concerted interaction of hypochlorous acid with the lysine and the glutamate residue should increase the electrophilicity of the chlorine species and in addition ensure the correct positioning of the chlorine species for the regioselective incorporation of chlorine into the indole ring of tryptophan.…”
mentioning
confidence: 99%
“…[10,11] The lysine residue is suggested to react with the hypochlorous acid to form a chloramine as the halogenating intermediate. [9] Flecks et al [11] suggested that a concerted interaction of hypochlorous acid with the lysine and the glutamate residue should increase the electrophilicity of the chlorine species and in addition ensure the correct positioning of the chlorine species for the regioselective incorporation of chlorine into the indole ring of tryptophan. Comparison of the amino acid sequences of flavin-dependent halogenases showed that the lysine residue is absolutely conserved, whereas the glutamate residue is conserved only in tryptophan halogenases.…”
mentioning
confidence: 99%
“…[10,11] Es wurde vorgeschlagen, dass der Lysinrest mit der hypochlorigen Säure zu einem Chloramin als halogenierendem Zwischenprodukt reagiert. [9] Flecks et al [11] postulierten, dass eine gleichzeitige Wechselwirkung der hypochlorigen Säure mit dem Lysin-und dem Glutamatrest die Elektrophilie der Chlorspezies erhöht und zusätzlich die korrekte Positionierung für den regioselektiven Einbau des Chloratoms in den Indolring des Tryptophans sicherstellt. Vergleiche der Aminosäuresequenzen Flavin-abhängiger Halogenasen haben gezeigt, dass der Lysinrest in allen Flavinabhängigen Halogenasen vollständig konserviert ist, der Glutamatrest dagegen nur bei den Tryptophan-Halogenasen.…”
Section: Professor Franz Lingens Zum 85 Geburtstag Gewidmetunclassified
“…[8] Extensive mechanistic investigation of these enzymes by both van PØe and Walsh, focusing predominately on tryptophan halogenases, has clarified their mechanism. [9] In short, they utilize FADH 2 supplied by a NAD-dependent flavin reductase to reduce oxygen to water with concomitant oxidation of halide to the corresponding hypohalous acid (HOX). This species migrates through a tunnel within the enzyme to form a stable chloramine adduct with an active-site lysine.…”
mentioning
confidence: 99%
“…[8] While FAD-dependent halogenases thus have the potential to improve a number of problems with current oxidative halogenation methods, they remain largely unexplored for preparative synthesis. Characterization of their activity in vitro has typically involved analytical scale reactions of tryptophan, [9] but van PØe and co-workers also explored the substrate scope of the tryptophan-7-halogenase PrnA expressed in Pseudomonas fluorescens (Scheme 2). [11] A variety of substituted indoles were accepted by the enzyme, but halogenation invariably occurred at the electronically most activated indole 2-position for all substrates except tryptophan.…”
mentioning
confidence: 99%